Masting mediated by summer drought reduces acorn predation in mediterranean oak forests (ECOLOGY, 2008)
Temporally variable production of seed crops by perennial plants (masting) has been hypothesized to be a valuable mechanism in the reduction of seed predation by satiating and starving seed consumers. To achieve these benefits, coexisting species subjected to the same predator would benefit from a similar pattern of seeding fluctuation over time that could lead to a reduction in predation at the within-species level. We tested for the existence of an environmental factor enforcing synchrony in acorn production in two sympatric Mediterranean oaks ( Quercus ilex and Q. humilis) and the consequences on within-species and between species acorn predation, by monitoring 15 mixed forests (450 trees) over seven years. Acorn production in Q. ilex and Q. humilis was highly variable among years, with high population variability (CVp) values. The two species exhibited a very different pattern across years in their initial acorn crop size ( sum of aborted, depredated, and sound acorns). Nevertheless, interannual differences in summer water stress modified the likelihood of abortion during acorn ripening and enforced within-and, particularly, between-species synchrony and population variability in acorn production. The increase in CVp from initial to mature acorn crop ( after summer) accounted for 33% in Q. ilex, 59% in Q. humilis, and 60% in the two species together. Mean yearly acorn pre-dispersal predation by invertebrates was considerably higher in Q. humilis than in Q. ilex. Satiation and starvation of predators was recorded for the two oaks, and this effect was increased by the year-to-year variability in the size of the acorn crop of the two species combined. Moreover, at a longer time scale ( over seven years), we observed a significant reduction in the mean proportion of acorns depredated for each oak and the variability in both species' acorn production combined. Therefore, our results demonstrate that similar patterns of seeding fluctuation over time in coexisting species mediated by an environmental cue ( summer drought) may contribute to the reduction of the impact of seed predation at a within-species level. Future research should be aimed at addressing whether this process could be a factor assisting in the coexistence of Q. ilex and Q. humilis.